(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Abstract In this paper, special attention will be paid to the importance of timely initiation of bankruptcy proceedings, ie the need for an efficient bankruptcy system which is a necessary part of the market economy of each country, as it provides security to creditors, recovery of companies with financial difficulties. The paper will explain the reasons that affect the delay and inefficiency of the bankruptcy procedure. On the other hand, the paper will explain the benefits of timely and efficient implementation of the bankruptcy procedure, whose main purpose is to satisfy the interests of all those who participate in it. Therefore, I will cover the special role of the Bankruptcy Trustee, which is especially evident after the legal consequences of the opening of the Bankruptcy procedure, where it protects the interests of the creditors and the bankruptcy debtor. Here, I will especially cover his special role as an authorized proposer in relation to filing a lawsuit for damages, ie damage suffered by creditors due to irresponsible behavior of the bankruptcy debtor, ie failure to file a proposal to open bankruptcy proceedings, which led to reduction of the bankruptcy estate from which the creditors are settled. The subject of research is the timely initiation and completion of the bankruptcy procedure in our law, as a procedure conducted by the Bankruptcy Trustee who is a professional in it. Meanwhile, the purpose of the research is to identify the disadvantages and advantages regarding the legal order of the bankruptcy procedure in terms of the responsibility of the management bodies for not submitting the proposal for opening the bankruptcy procedure.